La descentralización educativa en el Perú - Alvarez Laveriano, Neida (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
This essay introduces the educational decentralization as an important issue of the global public reform that become in different kinds of relationship between the State and the civil society. To precise this subject, this article develops conceptual distinctions among concepts close to the decentralization area. In addition,advantages and disadvantages of the decentralization are mentioned. At the last, the author analyzes the background and legislation of the Peruvian educational decentralization.

Este ensayo aborda la temática de la descentralización educativa, asumiéndolacomo parte de una reforma global del Estado y que establece relaciones diferentescon la sociedad civil. Para precisar esta temática, se presentan en primer lugar algunasdistinciones conceptuales claves entre la descentralización y otros términosrelacionados, así como las ventajas y desventajas de este proceso de descentralización.Posteriormente, se plantean los antecedentes y el contexto normativo de ladescentralización educativa en el Perú.
Keywords: Descentralización; Administración de la Educación; Política Educacional; Legislación Educacional; Educational Decentralization; Educational Administration; Education Policy; Educational Legislation; https://purl.org/pe-repo/ocde/ford#5.03.00